Metody ujmowania etyki biznesu w Polsce - Zadroga, Adam (Annales. Etyka w Życiu Gospodarczym, 2009)
From the beginning of the 1990s, a considerable interest in business ethics has been observed in Poland. It seems that the heritage of Polish researchers concerned with this academic discipline is already rich enough, and at the same time so diverse that it is worth making an attempt to systematize it, deepening and naming appropriate principle methods of grasping business ethics in Poland. The carried-out analyses allowed determining the following leading methods in the formal aspect: first, the metaethics of business ethics; second, business ethics grasped in the framework of various modifications of normative ethics (most often, deontology, utilitarianism, ethics of virtue and ethics of responsibility; on the other hand, it has been noticed that there is a complete lack of clear references to personalistic ethics); third, business ethics performed as etiology (descriptive ethics) in economic life.